Intersection of service and learning : research and practice in the second language classroom - Thompson, Gregory (Emerald Publishing Limited : Information Age Pub., 2012)
This book on service-learning provides a current view of service-learning research in the second language classroom and practical applications for the acquisition of both cultural knowledge as well as the different language modalities. This book helps in understanding how using service-learning in the language classroom can facilitate language acquisition. The author addresses many of the challenges faced by teachers in the second language classroom as they try to implement service-learning programs in their curriculum. Based on the research as well as the experience of the author and other practitioners in the field, suggestions are given in each chapter as to how to maximize student learning and acquisition of specific aspects of a language as well as on the formation of successful programs and service-learning experiences. These suggestions are integrated into the individual chapters based on the focus of the unit.This text shows how service-learning allows students real world application of the language they are learning in the classroom. This text discusses how service-learning assists students in contextualizing their learning and seeing the reality of their field of study and the applicability of their language classes to settings that they encounter in their own communities. Finally, at all levels teachers, professors, and administrators are being asked to provide standards and assessments to demonstrate achievement and excellence in their different fields. This text addresses how service-learning aids students in meeting these proficiency standards and helps them achieve many of the goals set forth by national and international foreign/second language learning organizations.